2014
DOI: 10.1186/1471-2407-14-838
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of nodular ground-glass opacities without percutaneous needle aspiration or biopsy

Abstract: BackgroundPercutaneous needle aspiration or biopsy (PCNA or PCNB) is an established diagnostic technique that has a high diagnostic yield. However, its role in the diagnosis of nodular ground-glass opacities (nGGOs) is controversial, and the necessity of preoperative histologic confirmation by PCNA or PCNB in nGGOs has not been well addressed.MethodsWe here evaluated the rates of malignancy and surgery-related complications, and the cost benefits of resecting nGGOs without prior tissue diagnosis when those nGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
(37 reference statements)
4
22
1
Order By: Relevance
“…The study indicated that with the increase of differentiation degree of invasive adenocarcinoma, the density and size of the lesions gradually increased, which were consistent with the Ref. [28][29] .…”
Section: Discussionsupporting
confidence: 84%
“…The study indicated that with the increase of differentiation degree of invasive adenocarcinoma, the density and size of the lesions gradually increased, which were consistent with the Ref. [28][29] .…”
Section: Discussionsupporting
confidence: 84%
“…This is because GGNs ≥ 15 mm, especially part-solid GGNs > 8 mm or their solid components ≥ 5mm have high malignant potential and thus are the candidates of surgical resection after prompt evaluation. [9][10][11][12] In conclusion, 3.3% of GGNs that had been stable during initial 3 years showed subsequent …”
Section: Discussionmentioning
confidence: 93%
“…12 Image data were reconstructed with a thickness of 1 to 3 mm. Images were obtained using a lung window setting with a level of -600 Hounsfield units (HU) and a width of 1500 HU, and a mediastinal window setting with a level of 30 HU and a width of 400 HU.…”
Section: Radiologic Evaluationmentioning
confidence: 99%
“…The resection criteria were as follows: (1) In pure GGNs < 10 mm, surgical resection should be considered if there is an increase in size ≥ 2 mm during 6 months of follow-up. (2) In pure GGNs ≥ 10 mm without significant changes in the initial 3 months of follow-up, we recommended surgical excision for GGNs ≥ 15 mm, whereas we recommended chest CT follow-up for one year or surgical excision for GGNs measuring 10-15 mm in size [22]. Each surgical specimen (entire tumor) was formalin fixed and stained with haematoxylin-eosin in accordance with routine regulations of the five hospitals, which were reviewed according to the new IASLC/ATS/ERS classification criteria, and tumor histologic subtypes were recorded.…”
Section: Methodsmentioning
confidence: 99%